1991
DOI: 10.1111/j.1349-7006.1991.tb01797.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in Tumor Blood Flow under Normotension and the Effect of Angiotensin II‐induced Hypertension

Abstract: To elucidate the significance of angiotensin II (AID‐induced hypertension chemotherapy, changes of tissue blood flow both in normal subcutis and in tumors (AH109A, LY80) were measured with the hydrogen gas clearance method. A newly‐developed anesthetic machine was used to keep the animals' condition constant. Tissue blood flow in normal subcutis and tumors always fluctuated with time under normotension. The nature and the rate of fluctuation in tumor Wood flow were almost identical in two different types of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 14 publications
2
36
0
Order By: Relevance
“…were given at 90-min intervals to maintain immobilization during the experiment. Enflurane concentration was maintained at 1% in the inhaled carrier gas at 1 l min 71 by means of an anaesthetic apparatus for small laboratory animals (Hori et al, 1991).…”
Section: Lymph Node Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…were given at 90-min intervals to maintain immobilization during the experiment. Enflurane concentration was maintained at 1% in the inhaled carrier gas at 1 l min 71 by means of an anaesthetic apparatus for small laboratory animals (Hori et al, 1991).…”
Section: Lymph Node Metastasismentioning
confidence: 99%
“…TBF was measured with the hydrogen clearance method (Hori et al, 1991(Hori et al, , 1996 whose principle was described in detail by Aukland et al (1964). In brief, after saturation of the tissue with hydrogen following inhalation of 9% hydrogen gas in air (at 1 l min 71 ), the blood flow value (in ml min 71 100 g 71 tissue) was calculated from the half-life of the clearance curve obtained.…”
Section: Measurement Of Tbfmentioning
confidence: 99%
“…However, in absolute terms, ATII has been found to increase blood flow in some tumours (Tokuda et al. 1990; Honr et al, 1991;Tanda et al, 1991) while decreasing it in others (Jirtle et al, 1978;Tozer and Shaffi, 1993). A decrease in absolute tumour blood flow could compromise delivery of drug to tumour microregions.…”
mentioning
confidence: 99%
“…Later, Jirtle et al (1978) found that constant intravenous infusion of high dose angiotensin 11 (1.4 Ag min ') into tumour-bearing rats caused a 4-fold increase in blood flow to the tumour growing in the mammary gland relative to that in the normal mammary gland and skin although the absolute blood flow to the tumour was decreased from 1.3 ml g -min ' to 0.8 ml g' min-'. Subsequent studies have shown that angiotensin IIinfusion can increase absolute, as well as relative, blood flow in some tumour systems (Tokuda et al, 1990;Hori et al, 1991;Tanda et al, 1991;Trotter et al, 1991).…”
mentioning
confidence: 99%